Emission from the circumgalactic medium: from cosmological zoom-in simulations to multiwavelength observables. Issue 2 (12th August 2019) - Augustin, R; Quiret, S; Milliard, B; Péroux, C; Vibert, D; Blaizot, J; Rasera, Y; Teyssier, R; Frank, S; Deharveng, J-M; Picouet, V; Martin, D C; et al.
ABSTRACT: We simulate the flux emitted from galaxy haloes in order to quantify the brightness of the circumgalactic medium (CGM). We use dedicated zoom-in cosmological simulations with the hydrodynamical adaptive mesh refinement code ramses, which are evolved down to z = 0 and reach a maximum spatial resolution of 380 h −1 pc and a gas mass resolution up to $1.8× 10^{5} \, h^{-1}\, \rm {M}_{\odot }$ in the densest regions. We compute the expected emission from the gas in the CGM using cloudy emissivity models for different lines (e.g. Lyα, C iv, O vi, C vi, O viii ) considering UV background fluorescence, gravitational cooling and continuum emission. In the case of Lyα, we additionally consider the scattering of continuum photons. We compare our predictions to current observations and find them to be in good agreement at any redshift after adjusting the Lyα escape fraction. We combine our mock observations with instrument models for Faint Intergalactic Redshifted Emission Balloon-2 (FIREBall-2; UV balloon spectrograph) and HARMONI (visible and NIR IFU on the ELT) to predict CGM observations with either instrument and optimize target selections and observing strategies. Our results show that Lyα emission from the CGM at a redshift of 0.7 will be observable with FIREBall-2 for bright galaxies (NUV∼18 mag), while metal lines like O vi and C iv will remain challenging to detect. HARMONI is found to be well suited to study the CGM at different redshifts with various tracers.